Soil and Water Conservation in sub-montaneous tract of Punjab - Bhatt, Rajan; Kukal, Surender Singh (Indian Farming, 2017)
Indigenous technical knowledge on soil and moisture conservation and crop production in Shiwaliks of Punjab has bore the test of time and has come to stay with the farmers. He is solving his day-to-day problems and is carrying on with technology now-how. However, increasing population along with demands and aspirations of the people has thrown challenges to the indigenous technology to meet newer challenges. Indigenous technology requires retesting in the light of scientific knowledge and modifying suitably so as to achieve higher production levels and more importantly to be adopted by the farmers of the area for an overall increment in their productivity and livelihood.